?G-RAFTING OF POLYBUTYL ACRYLATE GROWING CHAINS TO GELATIN (Biological Sciences - PJSIR, 2000)
Modification of gelatin by grafting with butyl acrylate in the presence of potassium persulfate is accomplished and the results are discussed with respect to percent grafting, grafting efficiency and rate of grafting. The number and variety groups along the chain of gelatin act as grafting centres. Grafting efficiency is found to be the same at all monomeric gelatin ratio.